Characterization of the polysaccharide from Bletilla striata and its inhibitory effects on amylolytic enzymes and prebiotic activity - ChunYan Fu; Xuefeng Deng; Jun Gao (Frontiers in Nutrition)
In the current study, a new polysaccharide named Bletilla striata polysaccharide (BSP) with an average molecular weight (Mw) of 85.4 kDa was obtained from B. striata. The inhibitory effects of BSP on α-amylase and α-glucosidase, as well as its prebiotic properties, were determined. The results showed that BSP was a neutral polysaccharide and is composed of mannose, glucose, and galactose with a relative molar ratio of 3.2:5.4:1.0. The main sugar residues in BSP were →4)-α-D-Glcp-(1→, →6)-β-D-Galp-(1→, →4)-β-D-Manp-(1→, and β-D-Manp-(1→. BSP displayed strong inhibitory effects against α-amylase and α-glucosidase and exhibited competitive inhibitory kinetics. At 4.0 mg/mL, the inhibitory rates of 67.75 ± 0.45% on α-amylase and 48.24 ± 1.02% on α-glucosidase were obtained, respectively. Moreover, BSP can serve as a carbon source to facilitate the proliferation of probiotics. These findings support the potential application of BSP in diabetes management.